The Extended Laboratory: new perspectives for the design of natural science education in digital contexts (Innovaciones Educativas, 2023)
The main objective of the essay is to explore several fundamental aspects of a teaching design model that seeks to revitalize experimentation as an essential element in the construction of scientific knowledge in formal education through digital technologies. The importance of the experience accumulated during Emergent Remote Teaching as a catalyst for change in education and as a source of inspiration for the development of the Extended Laboratory (EL) is highlighted. This model effectively adapts to the new hybrid or digital educational environments, offering theoretical answers to new needs and challenges in science education. It reflects on several fundamental ideas for the design of natural science teaching in digital contexts. Among them, the importance of the construction of a narrative context as an essential element in the design of experimental activities in the EL stands out. This narrative allows giving meaning to experimental activities and connecting them with discussions about professional practice and with socio-scientific issues. It also highlights the complexity of the task of constructing effective narratives in education, which involves numerous technical considerations: such as structuring the narrative, the use of various platforms, the definition of characters and scenarios, the creation of the narrative universe, and the relationship between the narrative and other elements of the teaching strategy. As a conclusion, a new perspective for the design of natural science education in digital contexts is presented, highlighting the importance of experimentation and the construction of effective narratives in education through laboratories.
Keywords: Natural science education; Digital education; Hybrid education; Experimental Activities; Technological Interfaces; Remote laboratory